Tournaments - O'Donoghue, P. (Modelling and simulation in sport and exercise, 2020)
This Chapter introduces the problems of designing tournaments, which not only depends on the performance and qualification of the involved athletes or teams but also: Sports tournaments can be organized as round-robin leagues, knockout competitions or a combination of both. There may be qualifying stages required due to restrictions on the number of participating teams or players. Tournament structures have changed to improve participation, revenues, entertainment value and safety. O`Donoghue discusses types of performance indicators, their meaning for tournament design and how modelling and Simulation of tournament dynamics can help to understand a tournament`s dynamic behavior and improve the adequacy of its design. He presents the main algorithms and data structures that are used to produce useful output information that is ultimately required by decision makers. Methods and indicators as dealt with in O`Donoghue`s chapter are also necessary for evaluating individual performance and success of players and teams.